THE CAUSATION OF EFFECTIVE ALTRUISM AS A CONDITION FOR THE DEVELOPMENT OF THE PUBLIC ORDER AFTER A PANDEMIC - Humeniuk, Yulia (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
Introduction.The article raises the question "What will be the public order after the COVID-19 pandemic?" The current situation makes it possible to draw analogies between anti-utopian novels such as "1984" by George Orwell, "Kallocaine" by Karin Boe, "The Glass Bees" by Ernst Junger. What these works of art have in common is that, as a result, interpersonal human relations, based on empathy, love, empathy, and care for one’s neighbor, become paramount to "save humanity", because only the presence of such feelings can preserve human life and moral values. Summarizing the achievements of the past, analyzing modern methodological concepts, and interpreting identical historical and philosophical material, we understand that the analysis of causal links between fear, the meaning of life, and altruism, including effective altruism, and the impact of this concept on the restoration of public order after a pandemic was the subject of scientific research. The aim and tasks. The purpose of this scientific investigation is to conduct an expanded analysis and identify the causal links between the nature of fear, the meaning of life, and altruism; to cover the modern understanding of effective altruism and solved due to this phenomenon the problems of development of public order in modern living conditions. Research methods. To achieve the aim and solve the problem of a particular problem used "explanatory" non-descriptive methodology: generalization achievements of the past along with the analysis of modern methodological concepts, interpretation of identical historical and philosophical material, creating a concept to solve the problem. Research results. Defining such a phenomenon as a "pandemic" and having characterized it, we get the answer to the question "What happens to the human immune system if the human body can not cope with the virus?"– the human soul isbeing suffered until it understands the essence of what is happening and, above all, the essence of its own existence. Based on this, the paper analyses the nature of fear, the meaning of life, altruism and identifies the links between these philosophical categories. The paper highlights the modern understanding of effective altruism and the possibility of solving the problem of bringing public order in modern conditions due to this phenomenon. Discussion. Analysis of the scientific achievements of philosophers and scientists in other branches of science at different times shows that interest like epidemics and pandemics has always existed. At the same time, the events surrounding the COVID-19 pandemic have led to a surge of scientific publications by both domestic and foreign researchers trying to find answers to the question of the future of humanity, which is currently experiencing moral decay and disorder. establishing public order in modern conditions. It became possible to study this problem and draw conclusions based on scientific works on the nature of fear, the meaning of life, and altruism.: P. Hajikurbanova, P. Haydenko, Rollo May, S. Kierkegaard, M. Heidegger, Y. Pustovoit; Democritus, L. Feuerbach, W. Frankl; O. Comte, M. Hoffman, R. Dawkins, W. Nemirovsky; P. Singer and W.Makaskil. Conclusion Thus, effective altruism is a social movement with its own philosophy, which uses facts, evidence, and reasoning in search of the most effective ways to improve the world and establish public order after the COVID-19 pandemic.